Theatre, education and performance the map and the story - Nicholson, Helen, 1958- (New York : Palgrave Macmillan, 2011)
"Theater education has often provided theatre-makers with radical new ways to encourage social participation and aesthetic engagement. This timely new book raises questions about how twentieth century practices have been revised in the twenty-first century, and how theatre-makers are finding new ways to engage young people in contemporary issues" --
Machine generated contents note: -- Mapping Stories -- PART I: Looking Back: Histories and Landscapes -- Spaces to Imagine: Theatre and Social Reform -- Spaces to Play: Childhood, Theatre and Educational Utopias -- Places to Learn: Activity and Activism -- PART II: Moving On: Theatre Education in the Twenty-first Century -- Traces and Places -- Globalisation and Regeneration: Re-branding Creativity -- Dramatising Home: Places of Safety and Risk -- 'This Island's Mine': National Identity and Questions of Belonging -- International Spaces: Global Citizenship and Cultural Exchange -- Changing Worlds: Performing Science, Theatre and Public Engagement -- Cool Spaces: Learning in Theatre and Beyond Theatres. -- Bibliography.
Includes bibliographical references and index.
Keywords: Theater and society; Drama in education; Theater and society -- Great Britain; Drama in education -- Great Britain; PERFORMING ARTS / Theater / General; PERFORMING ARTS / Acting & Auditioning